Publishing journal articles - Becker, Lucinda M., 1963-; Denicolo, Pam. (Los Angeles, Calif : SAGE, 2012)
Practical, no-nonsense, accessible guide to planning, writing and publishing a journal article.
Includes bibliographical references (p. [139]) and index.
Keywords: Academic writing -- Publishing; Academic writing; English language -- Rhetoric; Technical writing; Authorship -- Marketing